MECHANISMS FOR IMPROVING ENVIRONMENTAL COMPETENCE IN FUTURE TEACHERS (Academicia Globe: Inderscience Research, 2023)
This article reflects on providing environmental education and education to students, changing them in a positive way their attitude towards the environment and mother nature, preserving Mother Nature, mitigating the global environmental problems observed today and their negative consequences, including the lack of Water Resources, global climate changes and its impact on nature. In addition, the article discusses environmental competence in students and prospective teachers.